Nuclear pursuits : the scientific biography of Wilfrid Bennett Lewis - Fawcett, Ruth (McGill-Queen's University Press, 1994)
Born in England in 1908, Lewis earned a doctorate at the Cavendish Laboratory in 1934 and continued his research on nuclear physics there until 1939. During the war he worked on the development of radar and in 1945 became chief superintendent of the Telecommunications Research Establishment at Malvern. A year later he agreed to head Canada's fledgling nuclear research facility at Chalk River, Ontario, where he made his professional home for the next twenty-seven years. Lewis's drive, intelligence, and remarkable organizational skills placed him at the forefront of Canada's nuclear program. Convinced that nuclear energy could be used economically for generating electricity, Lewis fostered a collaboration between Atomic Energy of Canada Limited (AECL) and Ontario Hydro that led to the development of the CANDU reactor. CANDU has proven to be an efficient reactor whose performance compares very favourably with all other power reactors around the world. Lewis's efforts in developing this design, and his effective support of a strong tradition of basic research, are his most important legacies. Under his guidance, scientists at AECL achieved excellence in a number of fields and the laboratories have maintained those standards to the present. Though not every project he promoted came to fruition, and he seemed never to recognize the political aspects of the nuclear energy program, Lewis's influence on the development of science, technology, and industry in Canada and abroad was unique and profound. His story sheds new light on Canada's postwar science history, debates concerning national science policy, and growing international scientific collaborations. Nuclear Pursuits will be of interest to a wide audience, including scientists, engineers, historians of science and industry, and students of postwar Canadian history.